Integrating balance and postural stability exercises into the functional warm-up for youth athletes - Bird, S. P.; Stuart, W. (Strength and Conditioning Journal, 2012)
The goal of the functional warm-up is to stimulate sensory and motor components related to preparatory (feed-forward) and reactive (feed-back) systems through functionally integrated movement patterns. This article presents balance and postural stability exercises that are easily implemented into the functional warm-up as a movement preparation strategy for youth athletes.